A review on applications of bio-products employed in drilling fluids to minimize environmental footprint - Bichakshan Borah; Borkha Mech Das (Environmental Challenges, 2022)
The continuous growing requirement in energy and shrink in the production together calls for thrive in new technologies in the oil and gas industry. Understanding of drilling fluid properties aid to design a fluid system with better properties that can be useful for drilling non-traditional hydrocarbon reservoirs. Drilling fluids are colloids to which a numbers of additives have been added in order to perform some specific properties. Conventional chemical additives that are employed to regulate properties of drilling fluids pose various problems because of their environmental and personnel safety issues. Some of these additives are toxic, non-biodegradable and have a negative impact on the environment. The oil and gas industries produces a huge amount of spent drilling fluid, produced water, and accumulated drill cuttings from drilling operations, which are the sources of environmental pollution. Present day's environmental safety concerns are triggering the research and use of alternative multifunctional biodegradable and environmentally friendly drilling fluid additive. Hence comes the play of bio products to bypass these challenges. This review article is undertaken to highlight the application of some green bio products in drilling fluid to aid researchers and the oil and gas industry. This article also emphasizes how these bio products support in improvement of the drilling fluid properties while remaining cost effective.